Rolling Out the Red Carpet: Surviving High–profile Patients at Your Center - Nicholson, Amanda (Wildlife Rehabilitation Bulletin, 2013)
Admitting a well–known celebrity patient to a wildlife facility is not just about treating the animal—it is also about caring for the hundreds, sometime thousands of fans that come along with the patient! While it may seem like an additional hassle, ‘treating’ the fans is an important part of the rehabilitation process too. This article addresses how wildlife organizations can share stories through their websites as well as through Facebook and other social media tools. It also explores the idea of using webcams in a wildlife facility. Learn how to treat patients, raise money, and teach the world all at the same time.